Eficacia inhibitoria de ciprofloxacina ótica y doxiciclina sobre cepas de Prevotella intermedia: Estudio in vitro - Singo Salazar, Christian Andrés (2018)
Ciprofloxacin has been proposed as an alternative for local application in complementary therapy of periodontal treatment. Its topical (otic) form presents as a low cost and effective alternative against periodontopathogens. Objective: To determine the inhibitory effect of Ciprofloxacin otica (CIP) and Doxycycline (DOXI) on strains of Prevotella intermedia (Pi). Materials and methods: Experimental study, in vitro. The sample was consisted of cultures of Pi ATCC®25611 in Agar Mueller Hinton to determine by the antibiotic susceptibility test the inhibition halo. CIP-5ug / 10ul discs (G1 n = 10) were placed; DOXI-5ug discs (G2 n = 10); and, physiological saline discs-10ul (G3 n = 10). After 24 hours of incubation, halos were measured using Antibiotic Zone Scale (mm) with the parameters of the BD BBL Sensi-Disc Antimicrobial Suceptibibility Test Disc., With the following parameters: DOXI: resistant <12 mm, intermediate 13-15 mm, sensitive> 16 mm; CIPO: resistant <15 mm, intermediate 16-20 mm, sensitive> 21 mm. The Mann Whitney U test was used with a level of significance of 5%. Results: All the inhibition zones of both groups presented values higher tan the sensitivity parameters (100% effectiveness). Median for doxycycline was 38 mm and ciprofloxacin was 36 mm. There was a statistically significant difference for the G1 and G2 groups when compared with the reference values (p <0.05). Conclusion: Local ciprofloxacin demonstrated the same efficacy as doxycycline on strains of Prevotella intermedia.